Searching for Determinants of Support for Mini-Publics: Insights from a Polish Survey - Paulina Pospieszna (Polish Political Science Yearbook, 2025)
The erosion of liberal democracy has led to decreased civic engagement and trust in traditional institutions, prompting a search for innovative democratic solutions. Deliberative mini-publics, such as citizens’ assemblies, offer a promising avenue for addressing these challenges by engaging citizens in informed discussions and decision-making processes. However, research on these mechanisms in Central and Eastern Europe, particularly in Poland, remains limited. This study aims to fill this gap by examining Polish attitudes towards mini-publics and their potential to enhance democratic decision-making. Using data from a survey experiment conducted in February 2024, this study explores the relationship between satisfaction with democracy and other political attitudes toward support for minipublics. The findings suggest that individuals who perceive themselves as having influence over government actions are less likely to support mini-publics. Whereas satisfaction with democracy is positively linked with support for innovative decision-making mechanisms, socio-demographic factors do not have explanatory power. Overall, this research provides valuable insights for practitioners and scholars interested in promoting inclusive and participatory forms of governance in Poland and beyond.